Some notes about Herpetofauna of North middle Vietnam - Quang, Hoang Xuan; Thao, Hoang Ngoc; Sang, Nguyen Van (Academia Journal of Biology, 2014)
The North Middle Vietnam include from Thanh Hoa to Thua Thien - Hue province, It extends from 16o12’ - 20o40’N and 104o25’ - 108o10’E. An area is 51,500.7 km2. The results of survey have showed that 226 species of Amphibians and Reptiles belonging 26 families, 5 orders in the North Middle Vietnam. Among them, have 22 Amphibians and 15 Reptiles species is endemic of Vietnam. The Amphibians have 88 species, 27 genus, 8 families, family Ranidae is keep the upper hand with 34 species, 10 genus. Predominate genus is Rhacophorus (11 species) and Microhyla (10 species). The Reptiles have 138 species, 74 genus, 18 families, among them, family Colubridae is keep the upper hand with 53 species, 26 genus. Genus Trimeresurus is the most species (9 species). There are 46 species is complement for herpetofauna of North Middle Vietnam (13 Amphibians species, 33 Reptiles species - see table 2). There are 23 species in North Vietnam and 14 species in South Vietnam (Nguyen Van Sang, Ho Thu Cuc, Nguyen Quang Truong, 2005) have distribute to North Middle Vietnam (see section 2.2). A total of 226 species of Amphibians and Reptiles have 45 species are importance conservation: there are 27 species were listed in Vietnam Red Data Book 2007 (Critically Endangered: 3 species, Endangered: 13 species and Vulnerable: 11 species); 24 species in International Red Data Book (IUCN 2006 - Critically Endangered: 2 species, Endangered: 8 species, Vulnerable: 7 species, Near threatened: 7 species and Lower risk: 1 species); There are 15 species were listed in Decision Number 32/2006 of the Government of Vietnam, 2 species in Groups IB and 13 species in Groups IIB (see tables 3); and in CITES 2003, there are 13 species in App. II.